Faktor - Faktor Penyebab Laratnya Tb. Varco / Bg. Langkat Jaya Ix Di Area Berlabuh - Kurnianto (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2023)
On January 23, 2022, at Rede Muara Berau, the vessel TB. Varco/BG. Langkat Jaya IX was at anchor and experienced several problems, including poor weather conditions and limited visibility, which resulted in the vessel being stranded and the boat drifting. This research aims to determine what factors influenced the stranding of the vessel and to assess its impact on the seabed in the then muddy waters of Muara Berau. In this scientific research, the research method used is a descriptive method to identify and explain the causes that arise and the effects they cause, so as to answer the formulation of the problem that has been set, namely the factors and their impacts on the seabed. Based on research conducted by the author while on board the TB. Varco/BG. Langkat Jaya IX, related to the analysis of ship stranding, it was found that there were problems, including external factors and internal factors that caused the ship to be stranded. From the results of the above research, it can be concluded that the factors that cause ship stranding include ocean currents, waves, wind, seabed, weather, tides, anchors, anchor chains, windlass, draft, and human error. The seabed in the form of mud makes the ship stranded because it cannot properly reinforce its anchor performance when at anchor. The author's suggestion is that the first action to take is to increase the length of the anchor chain, and if the problem cannot be solved, then the ship's main engine should be used. The captain should, before running the anchor, determine the length of the chain to be used, select the appropriate type of seabed, and pay attention to the water depth. Keywords : Anchor, Bad Weather, Shipwreck, Wire ropejangkar.